Optimal Bioeconomic Exploitation of the Demersal Fishery in Northwest Peninsular Malaysia - Tai, Shzee Yewi (Universiti Putra Malaysia Press, 1996)
The optimal bioeconomic rate of exploitation of the demersal fishery in northwest Peninsular Malaysia (NWPM) is determined in this paper. A bioeconomic model for the fishery is developed and estimated. The results show that even though present rate of exploitation of the demersal fishery shows slight improvement compared to the open access level, the demersal stock is over fished biologically and economically at this rate. An important result is that tremendous improvement for the demersal fishery in WPM can be achieved if fishing effort is reduced by 60 to 78 percent from the present level. This implies an urgent need to formulate appropriate effort reduction management policies in order to derive maximum benefits from the fishery.